MODEL PENYEBARAN SEKUENSIAL DUA STRAIN VIRUS INFLUENZA A DENGAN MEKANISME ANTIGENIC DRIFT - , DIANITA PUTRI ARMY, Dr. Fajar Adi Kusumo, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Flu is one of the respiratory disease caused by influenza virus A. Antigenic drift mechanism changed the virusâs structure in phase and created two strains of influenza virus A which is simultaneously infected humans. Mathematical modeling can be used to explain epidemiology of two strains of influenza virus A infection. Here we discuss the sequential transmission model of two strains influenza virus A with antigenic drift mechanism. There are six equilibrium points obtainable from the model and we analyze the stability of each equilibrium points. The explanation of the model equipped with simulation which described each equilibrium points in face portrait.